Improved method for the obtaining DTTA-appended 2,2’-bipyridine ligands for lanthanide cations - Dmitry S. Kopchuk; Alexey P. Krinochkin; Мaria I. Valieva; Еkaterina S. Starnovskaya; Yaroslav K. Shtaitz; Svetlana S. Rybakova; Evgeny D. Ladin; Ekaterina A. Kudryashova; Elvira R. Sharafieva; Оleg N. Chupakhin (Chimica Techno Acta)
The composition of the reaction mixture after DTTA tert-butyl ester alkylation with 6'-halomethyl-5-phenyl-2,2'-bipyridines was studied. In addition to the target product, DTTA-appended 2,2’-bipyridine, the corresponding 6'-hydroxymethyl-substituted 2,2’-bipyridine and (5'-phenyl-[2,2'-bipyridin]-6-yl)methyl formate were isolated as by-products in some cases. Finally, an improved procedure for the DTTA tert-butyl ester alkylation with 6'-halomethyl-5-phenyl-2,2'-bipyridines by using Finkelstein reaction was developed.